Assessment of enterprise activity effectiveness - Yangming, Zhang (Харківський національний автомобільно-дорожній університет, 2024)
In the diploma work, the concept of "efficiency of activity" has been improved, which, in contrast to the existing ones, characterizes it as the ability of the subject of activity to determine and achieve goals that reflect the optimal ratio of resources spent and results of activity. The methodological approach to assessing the efficiency of the enterprise, which, unlike the existing ones, is based on the definition of local, block and integrated assessments of the effectiveness of activity on the basis of using the matrix method. The opening of an online store of the enterprise and the reduction of its transport costs by improving the operational management of transportation are proposed and substantiated. Forecast assumptions regarding the development of the object of study are a steady increase in the efficiency of the enterprise.
Keywords: efficiency; efficiency of activity; matrix approach; online store; transportation costs